CAR T CELL THERAPY - Dr. Renuka; Dr. Juhi Aggarwal; Dr. Eram H. Pasha (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
CAR T cells refer to T lymphocytes that undergo genetic engineering to generate artificial T cell receptors, serving a crucial role in immunotherapy1. Chimeric antigen receptors (CARs) are specialized cell-surface receptors designed to identify specific proteins (antigens)2. These receptors, considered chimeric because they incorporate components from various receptors, are created by extracting T cells from the patient and modifying them in a laboratory setting3. The modified T cells then display chimeric antigen receptors, or CARs, on their surface.